Leisure practices of students (in the context of distance learning) (The Journal of Psychology and Sociology, 2021)
The article examines the practice of spending free time for students of social sciences and humani- ties, namely students in the specialty of sociology and social work. Particular attention is paid to the impact of the pandemic, and changes in the educational process, namely distance education on the leisure practices of young people.The purpose of the study is to develop a number of recommendations on the positive influence of youth leisure practices on the development of their personal and professional qualities, to identify the features and structure of students’ leisure and reading practice.The scientific significance of this study is due to the comprehensive consideration of students’ lei- sure time, including reading. A literature review of studies by foreign and domestic scientists on this topic was carried out. The practical significance of this work lies in the fact that it can become the basis for future research in accordance with the problem under study.The paper presents the results of an online survey conducted among students in grades 1-4 in the specialties of sociology and social work. As a result of the study, the structure of youth leisure practices and the main factors influencing them were identified. In addition, the current state of the students’ read- ing practice was determined.The research results can be used by universities in the development of activities for the rational organization of students’ leisure, to improve the reading practice of students, as well as in teaching such disciplines as youth sociology, social work with youth.Key words: free time, leisure practices, practice of reading books, hobbies.